PENGARUH PENYARADAN TERHADAP KERUSAKAN TEGAKAN TINGGAL PADA BERBAGAI TINGKAT KELERENGAN - Dulsalam Dulsalam; Sukanda Sukanda (Jurnal Penelitian Hasil Hutan, 1988)
An investigation  or  the  effect  of  skidding   to  residual  stand  damage  on  several  slope  degrees  has  been  done  at PT Sumpol Timber  in South  Kalimantan in 1987.  The purpose  of  this investigation  is to seek  information   on the residual stand  damage  caused  by  skidding   on  several slope  degrees.  The  investigation   took  place  in three  different  slope  degrees: i.e.:  0  -  20  %, 20 - 40  %, and > 40%.  Sample  plots  were selected with  completely randomized   design.Results  of  this investigation  are concluded  as follows   :Skidding has caused part  of  the  residual stand  to damage.The  residual  stand  damage  caused  by  skidding   ranges from 10  Trees/ha to 70 trees/ha  (from 6 % to 29  %)  with an average of 30  trees/ha  (15%) with  standard  error of  3,60   trees/ha. The  residual stand  damage caused   by skidding  on  :             a. 0 - 20 % slope  ranges from 10  trees/ha  to 50  trees/ha (6 – 18%) with an average of 23,3  trees/ha  (11 %).             b. 20 - 40  % slope  ranges  from  10  trees/ha  to  70 trees/ha  with  an average of  30  trees/ha  (15 %).              c.Greater  than 40  %  slope  ranges from  20  trees/ha  to  70 trees/ha   (from 10 % to 29 %) with an average of 38 trees/ha (19 %).The  result  of  Least  Significant   Difference   (LSD) test  on  the  data  revealed  that  the residual stand  damage  between 0 - 20% and > 40%  slope  differs  significantly at 95% level.    The higher the slope degree the greater the residual stand damage took  place.It  is therefore  sugessted  that  skidding  on 40  % slope  degree  or more  be done  with  great  care in order  to decrease  the residual stand  damage